Artificial Intelligence for Autonomous Robotic Surgery in Urology: A Narrative Review - Dae Young Lee; Hee Jo Yang (Urogenital Tract Infection)
Artificial intelligence (AI) has emerged as a transformative force in various sectors, including medicine, where it processes high-dimensional data to improve diagnostics and treatment outcomes. This review explores AI applications in urological surgery, highlighting advancements such as image classification and robotic assistance in surgical procedures. AI has demonstrated exceptional diagnostic accuracy, with some systems achieving up to 99.38% in detecting prostate cancer. Additionally, AI facilitates real-time anatomical recognition and instrument delineation, increasing surgical precision. While current robotic systems operate under human supervision, ongoing research aims to advance autonomous surgical capabilities. The future of AI in robotic surgery is promising, especially regarding the possibility of improved outcomes; nonetheless, challenges related to autonomy, safety, and ethics remain.